Analisis Strategi Bauran Pemasaran berdasarkan Prinsip Syariah (Studi Kasus: Meryva Shop di Kulonprogo, Yogyakarta): (Marketing Mix Strategy Analysis based on Sharia Sharia Principles (Case Study: Meryva Shop in Kulonprogo, Yogyakarta)) - Isti Fadah; Desva Kansa Vijonta; Septarina Prita Dania Sofianti; Istatuk Budi Yuswanto (UPT Penerbitan Universitas Jember, 2022)
This study aims to determine and analyze the suitability of the application of the marketing mix at Meryva Shop with sharia principles. This marketing mix consists of product (product), price (price), place (place), & promotion (promotion) which is often referred to as the 4Ps. Meryva Shop is one of the Micro Small and Medium Enterprises (UMKM) which is engaged in the culinary and textile businesses. Some of its products in the culinary field are Drinkita, Snackita, and Iki Suki; Meanwhile, for the textile sector, women's clothing is varied, namely, pajamas and negligee suits. Meryva Shop has 2 places to run its business, namely through anstore offline located at Ndalem Giripeni Housing 106, Kulonprogo, and anstore online using theplatform Shopee. The method used in this research is qualitative. This study uses primary and secondary data with interviews, observations, and documentation as data collection techniques. The informants used are the owner of the Meryva Shop itself and several of its customers. The results of this study indicate that the application of the four marketing mixes at Meryva Shop, namely the product mix, price, place/distribution channel, and promotion is in accordance with sharia principles. Keywords: Culinary, Marketing Mix, Meryva Shop, Sharia Principles, Textile.